Low luminance visual acuity in patients with central serous chorioretinopathy. (10th September 2012) - Fujita, Kyoko; Shinoda, Kei; Matsumoto, Celso Soiti; Imamura, Yutaka; Mizutani, Yoshihiro; Tanaka, Etsuko; Mizota, Atsushi; Oda, Koichi; Yuzawa, Mitsuko
<x xml:space="preserve">Abstract</x> Background The aim was to determine the low luminance visual acuity in eyes with central serous chorioretinopathy. Methods Seven eyes of seven patients with central serous chorioretinopathy and six eyes of six age‐matched normal volunteers were examined. Low luminance visual acuity charts were created by an Apple Power Mac G5 computer and displayed on a cathode ray tube monitor (SONY GDM‐F500). The background luminance was set at six different levels from 78.20 cd/m2 to 0.37 cd/m2. The visual acuities of the eyes with central serous chorioretinopathy at each of the six luminance levels were compared to those from their fellow eyes and to normal eyes. Results The mean visual acuities varied from 0.13, 0.23, 0.29, 0.42, 0.62 to 0.70 logMAR units as luminance varied from high to low. At the lowest luminance (0.37 cd/m2), five of the seven eyes could not read any character. The mean visual acuities of the fellow eyes at the same luminance levels were 0.03, 0.06, 0.11, 0.20, 0.27 and 0.45 logMAR units and those of the normal volunteers were 0, 0.03, 0.08, 0.14, 0.23 and 0.38 logMAR units, respectively. The visual acuities of the eyes with central serous chorioretinopathy were significantly poorer than those of the normal eyes at all luminance levels except 0.37 cd/m2(p < 0.05 for all). Conclusions Although the eyes from all three groups had 0 logMAR units visual acuity under standard testing condition, the visual acuity of the eyes with central serous chorioretinopathy were significantly worse at low luminance levels. The low luminance visual acuity may provide information on the visual disturbances reported by central serous chorioretinopathy patients with 0 logMAR units visual acuity.